The Efficacy and Safety of Ixazomib for Newly Diagnosed Multiple Myeloma (NDMM) and Refractory or Relapsed Multiple Myeloma (RRMM): An Updated Systematic Review - Lubis, Ainun Basyiroh; Santosa, Damai; Rizky, Daniel; Tandarto, Kevin; Kartiyani, Ika; Yunarvika, Vina; Ardini, Desta Nur Ewika; Setiawan, Budi; Pangarsa, Eko Adhi; Suharti, Catharina (Indonesian Journal of Cancer, 2025)
Background: Newly diagnosed multiple myeloma (NDMM) is a significant healthcare concern, comprising 1.8% of newly diagnosed cancers in the United States. Recent advancements in NDMM and refractory/relapsed multiple myeloma (RRMM) treatment, including novel agents like ixazomib, have improved patient outcomes. Ixazomib, an oral proteasome inhibitor, has shown promise in clinical trials, particularly in combination with lenalidomide and dexamethasone (IRd). This study aims to find the efficacy and safety profiles of ixazomib for NRMM and RRMM.Methods: We conducted a systematic literature review using Scopus, PubMed, Google Scholar, and ProQuest databases, focusing on randomized controlled trials (RCTs) evaluating ixazomib’s efficacy and safety in NDMM and RRMM treatment. Eligibility criteria included studies published within the last 3 years reporting data on ixazomib in NDMM and RRMM patients. Quality assessment utilized the Cochrane Risk of Bias tool for RCTs.Results: The review identified three studies from 2021–2023 demonstrating ixazomib’s efficacy and safety in MM treatment across various patient groups. Benefits included improved progression-free survival (PFS) in non-transplant NDMM, significant PFS advantage in relapsed/ refractory MM, and efficacy in transplant-ineligible NDMM induction regimens.Conclusion: Ixazomib emerges as a well-tolerated maintenance therapy offering significant PFS advantages in NDMM and RRMM, irrespective of age or frailty status. Future research, including multicenter studies, is warranted to further elucidate ixazomib’s role in MM management.